2022
DOI: 10.1097/gco.0000000000000773
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of placenta accreta spectrum

Abstract: Purpose of reviewPlacenta accreta spectrum (PAS) is a major cause of severe maternal morbidity. Perinatal outcomes are significantly improved when PAS is diagnosed prenatally. However, a large proportion of cases of PAS remain undiagnosed until delivery.Recent findingsThe prenatal diagnosis of PAS requires a high index of suspicion. The first step is identifying maternal risk factors. The most significant risk factor for PAS is the combination of a prior caesarean delivery and a placenta previa. Other major ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Ultrasound (US) examination and magnetic resonance imaging (MRI) interpretation for accurate antenatal diagnosis should be done by an experienced radiologist. US is usually the rst imaging modality for the prenatal diagnosis of PAS and can be highly accurate when performed by a provider with expertise [19]. MRI is usually performed when PAS is suspected by US studies mostly with the aim of evaluating the extent of placental invasion, specially for those cases of posterior lying placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound (US) examination and magnetic resonance imaging (MRI) interpretation for accurate antenatal diagnosis should be done by an experienced radiologist. US is usually the rst imaging modality for the prenatal diagnosis of PAS and can be highly accurate when performed by a provider with expertise [19]. MRI is usually performed when PAS is suspected by US studies mostly with the aim of evaluating the extent of placental invasion, specially for those cases of posterior lying placenta.…”
Section: Discussionmentioning
confidence: 99%
“…PAS is an infrequent disorder and the number of cases described is still small. Nevertheless, this report describes one of the larger published case series until the present moment [13,[17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the endometrium is thought to prevent normal decidualization, causing abnormally deep placental villi and trophoblastic invasion and thus leading to the development of PAS [ 10 ]. Other risk factors for PAS include placenta previa, prior cesarean section, intrauterine procedures, use of assisted reproductive technology, a history of PAS, a history of PPH, and twin gestation [ 11 ]. Other reports have indicated that smoking is a risk factor for PAS [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 In fact, the presence of placenta previa (PP) and a history of previous cesarean deliveries are the two major risk factors for PAS, and the incidence increases linearly with the number of repeated cesarean deliveries or hysterotomies. 4 , 5 PP at one stage was considered necessary in PAS diagnosis. 6 Such antenatal situations (PP and PAS) could be associated with high maternal and neonatal morbidity and even mortality.…”
Section: Introductionmentioning
confidence: 99%